Pop Up Book Media to Improve Disaster Literacy in “Kurikulum Merdeka” - Risky Dwi Cahya; Dholina Inang Pambudi; Romi Febri; Nurfauzan Wahid (Universitas Negeri Padang, 2023)
Understanding by Design (UBD) is a recommended learning model in the independent learning curriculum. The issue in this study is that Indonesia is a country of a million disasters so it is important to have broad insights related to disasters and their mitigation. The reality is that students still lack insight into disasters and their mitigation. The purpose of the study was to improve the disaster literacy of students using the UBD learning model with pop-up book media. Quantitative methods were used in the study. The population in this study was SD N Experimental Padang, West Sumatra which had a sample of 42 students divided into a control class and an experimental class. The result of the application of the UBD model is the result of statistical analysis with a t-test showing that the value of the t coefficient is 19,252 with a df of 20 and a p-value of 0.00. The coefficient is p-value<y= 0.05. Demikian, it can be concluded that the test rejects H0 or accepts H1. The test results have a significant influence on UBD's learning model with pop-up book media on increasing student disaster literacy. The conclusion of this study is to use the UBD learning model with pop-up book media to increase disaster literacy in elementary school students.